Analysis of Electrical Power Consumption in Container Crane of Container Terminal Surabaya - A.A. Masroeri; Eddy Setyo Koenhardhono; Fathia Fauziah Asshanti (International Journal of Marine Engineering Innovation and Research, 2017)
Container crane electrification is a re-powering process of container cranes from diesel to electricity. In electrification process, it is required an analysis of electrical power consumption that is needed in the operational of container crane. It aims to determine whether the amount of electrical power that is supplied by PLN can be optimally used in the operational of container crane to do loading and unloading activities. To perform the analysis of electrical power consumption, it is required various data and calculations. The required data are container crane specifications and other electrical equipment specifications, the amount of electrical power that is supplied by PLN, also the single line diagram from the electrical system at the port. While, the calculations that is needed to be performed are the calculation of electrical power load in motors and other electrical equipments, the calculation of nominal current and start current, the selection of cable and busbar, and the calculation of wiring diagram junction power. From the calculations that has been done, then the next step is to do the load flow analysis simulation by using software simulation, so an accurate and effective load flow analysis can be obtained to optimize loading and unloading activities at the port. The result of this research, it can be seen that container crane electrification will give advantages in both technical and economical for the company and for the ship, such as accelerate the loading and unloading time of containers and reduce idle time, especially in the operational of diesel generator.